2023
DOI: 10.3390/microorganisms11051171
|View full text |Cite
|
Sign up to set email alerts
|

A Higher Abundance of Actinomyces spp. in the Gut Is Associated with Spontaneous Preterm Birth

Abstract: Preterm birth is a major challenge in pregnancy worldwide. Prematurity is the leading cause of death in infants and may result in severe complications. Nearly half of preterm births are spontaneous, but do not have recognizable causes. This study investigated whether the maternal gut microbiome and associated functional pathways might play a key role in spontaneous preterm birth (sPTB). Two hundred eleven women carrying singleton pregnancies were enrolled in this mother-child cohort study. Fecal samples were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Streptococcus was the predominant genera in our preterm BM samples, whereas the abundance of Staphylococcus was lower than previously reported [ 21 ]. In a case–control study examining the gut microbiota of 121 mothers with vaginal deliveries, the mothers giving birth prematurely were found to have lower abundance of Streptococcus , four days postpartum [ 82 ], whereas another study reported a higher abundance of Streptococcus in the gut microbiota of mothers who deliver preterm before delivery [ 83 ]. Evidence also suggests that PTB is associated with maternal Group B Streptococcus (GBS) colonization worldwide, previous work from SMRU suggests a low proportion (12%) of mothers carry Group B Streptococcus at birth [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus was the predominant genera in our preterm BM samples, whereas the abundance of Staphylococcus was lower than previously reported [ 21 ]. In a case–control study examining the gut microbiota of 121 mothers with vaginal deliveries, the mothers giving birth prematurely were found to have lower abundance of Streptococcus , four days postpartum [ 82 ], whereas another study reported a higher abundance of Streptococcus in the gut microbiota of mothers who deliver preterm before delivery [ 83 ]. Evidence also suggests that PTB is associated with maternal Group B Streptococcus (GBS) colonization worldwide, previous work from SMRU suggests a low proportion (12%) of mothers carry Group B Streptococcus at birth [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, increased abundance of Actinomyces have been reported in those with depression, Crohn’s disease, and SARS-CoV-2 infections ( Barandouzi et al, 2020 ; Farsi et al, 2022 ; Pittayanon et al, 2020 ). During pregnancy, Actinomyces infections appear to be rare, but increased abundance of Actinomyces species is associated with increased risk of spontaneous preterm birth ( Yu et al, 2023 ). Therefore, our results contrast with the extant literature reporting Actinomyces .…”
Section: Discussionmentioning
confidence: 99%